1998
DOI: 10.1289/ehp.98106s61589
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of soilborne lead in adults, by stable isotope dilution.

Abstract: Using stable isotope dilution, we determined the bioavailability of soilborne lead (Pb) in human adult volunteers. Soil from a residential yard at a mining-impacted federal Superfund site that had negligible amounts of other priority pollutants was dried and screened through a 25-pm mesh sieve. The <250-pm fraction, which likely represents that ingested via hand-to-mouth activity, was then sterilized by exposure to radiation. Ten replicate samples yielded a mean (SD) soil Pb concentration of 2924±36 ppm, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 20 publications
2
88
0
2
Order By: Relevance
“…Significant differences (p=0.0008) between all methods, including the in 4 vivo study by Maddaloni et al (1998) [8] , were obtained. The bioaccessibility values from all 5 small intestinal digestions were higher than the in vivo bioavailability results (Figure 3).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Significant differences (p=0.0008) between all methods, including the in 4 vivo study by Maddaloni et al (1998) [8] , were obtained. The bioaccessibility values from all 5 small intestinal digestions were higher than the in vivo bioavailability results (Figure 3).…”
mentioning
confidence: 83%
“…The amount of soil and the meal was based on the study presented by Maddaloni et al [8] . One 8 hundred milligrams of soil were introduced in the model with 240 mL of water or the standard 9 breakfast from the in vivo study to study the fasted and fed situation, respectively.…”
Section: Methods E Din 19738 (Germany) the German Methods E Din 19738 mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this, the isotopes and their ratios (between themselves, including the 204 isotope) may be applied to the recognition of the Pb ore which was used to produce the material (Scheuhammer and Templeton, 1998;Scheuhammer et al, 2003;Thomas et al, 2009). Knowing these isotopic ratios in various materials, it is possible to compare them with values found in biological samples to recognize the possible pollutant connection (Maddaloni et al, 1998;Scheuhammer et al, 2003;Svanberg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having more opportunities for oral exposure to contaminated dust and soil, children may absorb a greater proportion of ingested lead than adults (ATSDR, 1999). A study of adults residing near a National Priorities List (NPL) site indicated that the bioavailability of ingested soil-borne lead in adults was approximately 26% (Maddaloni et al, 1998). Based on lead absorption studies, the predicted bioavailability of ingested soil-borne lead in children ranged from 25% to 41% (Ziegler et al, 1978;Casteel et al, 1997;ATSDR, 1999).…”
Section: Introductionmentioning
confidence: 99%